Work motivation and work environment as a trigger for increased employee performance - Karlita, Ega Serli; Zaelani, Rizky; Anggrai, Fani; Amaria, Lilis Handayani; Haryadi, Didit (Trigin Publisher, 2024)
Effective management, thinking about the importance of human resources. Employee performance is an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used an associative descriptive quantitative method with a population of 42 respondents drawn into a sample using non-probability sampling, using the saturated sampling / total sampling method. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that work motivation significantly influences employee performance. The second hypothesis states that the work environment substantially affects employee performance. The third hypothesis is that employee performance is influenced by work motivation and work environment, which can simultaneously improve employee performance. This research is expected to provide theoretical contributions to the literature in this context, certainly in the context of human resource management